Taxonomic significance of microlepides on subimaginal tarsi of Ephemeroptera - Kluge, Nikita J. (Zootaxa, 2022)
In each mayfly individual, the surface of the subimaginal cuticle significantly differs both from imaginal and larval cuticles, being different on different parts of the body. Most of the subimaginal body, including femora and tibiae, is covered with microtrichia. Tarsal segments are either also covered with microtrichia, or their microtrichia are transformed into microlepides of various shapes. The most usual forms of microlepides are the pointed and the blunt ones. Arrangements of microtrichia, pointed microlepides, blunt microlepides and other forms of microlepides on certain tarsomeres represent good taxonomic characters, which in some cases allow characterization of high level taxa, and in some cases distinguish closely related species. Arrangement of microlepides and microtrichia on subimaginal tarsi of examined mayfly species is given. The following new synonyms are proposed: Afroptilum boettgeri (Kopelke 1980) = Xyrodromeus africanus Lugo-Ortiz & McCafferty 1997, syn. n.; Labiobaetis vinosus (Barnard 1932) = L. tenuicrinitus (Kopelke 1980), syn. n.; Baetis parvulus Crass 1947 = Baetis permultus Kopelke 1980, syn. n.; Epeorus gilliesi Braasch 1981 = Epeorus petersi Sivaruban et al. 2013, syn. n.; Dicercomyzon femorale Demoulin 1954 = Dicercomyzon costale Kimmins 1957, syn. n.